Kajian Analisis Standar Belanja Pemerintah Kota Batu - Dewi Noor Fatikhah Rokhimakhumullah (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this study was to determine the costing and budgetary allocation to each unit of work efficiently and effectively in order to be a reference to any programs / activities of the same and get the Standard Model analysis of spending, according to the characteristics of the program / activity in Batu. This study produced 16 models of standard analysis of the overall expenditure SKPD. . From these results, it can be concluded that by using the ASB, Batu City Government can determine the reasonableness of spending to carry out an activity in accordance with task, principal, and function; minimize the expense of the less obvious inefficiencies resulting budgets, increase efficiency and effectiveness in the management of the Regional Finance, determination budget based on clear performance benchmarks, units get greater freedom to determine its own budget. Keywords: Analysis of Standard Spending, Financial Management, Government of Batu City